Wide-temperature-range ester-based electrolyte and application thereof in aqueous zinc ion battery

By using a wide-temperature domain ester-based electrolyte containing diethylene glycol ether acetate and ammonium o-sulfobenzoate in aqueous zinc ion batteries, the problems of zinc dendrites growth and zinc negative electrode corrosion are solved, and the circulation performance and service life of the battery are significantly improved.

CN119542574AActive Publication Date: 2025-02-28HEFEI WATER DEPARTMENT ENERGY TECHNOLOGY CO LTD

Patent Information

Application Number
CN202411722356.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-28
Publication Date
2025-02-28
Estimated Expiration
2044-11-28

AI Technical Summary

Technical Problem

Water-based zinc ion batteries have problems with zinc dendrites, side reactions and zinc negative electrode corrosion, resulting in low Coulomb efficiency and shortened battery life.

Method used

A wide temperature domain ester-based electrolyte is used, including zinc salt, deionized water, organic solvents and organic salt additives, and the specific composition is diethylene glycol ether acetate and ammonium o-sulfobenzoate, and it is mixed uniformly by stirring and sonication.

Benefits of technology

Effectively inhibit the growth of zinc dendrites, improve the corrosion phenomenon of zinc negative electrodes, and improve the stability and service life of the battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119542574A_ABST
    Figure CN119542574A_ABST
Patent Text Reader

Abstract

The invention discloses a wide-temperature-range ester-based electrolyte, and relates to the technical field of aqueous zinc ion battery electrolytes, and the electrolyte comprises the following components: a zinc salt, deionized water, an organic solvent and an organic salt additive; the organic solvent is diethylene glycol monoethyl ether acetate; the organic salt additive is o-sulfobenzoic acid ammonium. The invention also discloses an application of the wide-temperature-range ester-based electrolyte in an aqueous zinc ion battery and the aqueous zinc ion battery. The electrolyte can inhibit the growth of zinc dendrites, improve the corrosion phenomenon of a zinc negative electrode related to active water, realize effective protection of the zinc negative electrode, greatly improve the cycle performance stability and prolong the service life of the aqueous zinc ion battery.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of aqueous zinc ion battery electrolytes, and in particular to a wide temperature range ester-based electrolyte and application thereof in aqueous zinc ion batteries. Background Art

[0002] Widespread reliance on fossil fuels and growing energy demands are driving the development of an energy economy in a cleaner and sustainable manner. Aqueous zinc-ion batteries (AZIBs) have attracted widespread attention not only because of their low cost, which is much cheaper than lithium-ion batteries (LIBs) electrolytes, but also because they are intrinsically safe and environmentally friendly, with high theoretical volumetric / gravimetric capacity (5855 mAh cm -3 , 820mAh g -1 ), non-toxicity and abundance (roughly 300 times the amount of lithium), and the prospect of being easily mass-produced.

[0003] However, even though zinc metal offers a high hydrogen overpotential that enables its immediate use as an electrode in aqueous electrolytes, its low redox potential (-0.76 V vs standard hydrogen electrode) makes the hydrogen evolution reaction (HER) on the surface inevitable. At the same time, aqueous zinc-ion batteries also suffer from many challenges, such as severe side reactions, parasitic hydrogen evolution, and zinc dendrite growth, leading to low Coulombic efficiency (CE) and shortened battery life. In particular, the growth of zinc dendrites not only leads to rapid capacity decay, but also reduces the reversibility of the zinc anode, thereby accelerating battery failure. These have seriously hindered the large-scale application of aqueous zinc-ion batteries. Summary of the invention

[0004] In order to solve the above technical problems, the purpose of the present invention is to provide a wide temperature range ester-based electrolyte and its application in aqueous zinc ion batteries, which can inhibit the growth of zinc dendrites, improve the corrosion phenomenon related to the zinc negative electrode and active water, achieve effective protection of the zinc negative electrode, and greatly improve the cycle performance stability and service life of the aqueous zinc ion battery.

[0005] The technical solution of the present invention to solve the above technical problems is as follows: a wide temperature range ester-based electrolyte is provided, comprising the following components: zinc salt, deionized water, an organic solvent and an organic salt additive; wherein the organic solvent is diethylene glycol ethyl ether acetate; and the organic salt additive is ammonium o-sulfobenzoate.

[0006] Furthermore, the zinc salt is zinc perchlorate hexahydrate, and the concentration in the electrolyte is 0.5-3 mol / L.

[0007] Furthermore, the volume fraction of the organic solvent in the electrolyte is 20%-60%.

[0008] Furthermore, the concentration of the organic salt additive in the electrolyte is 0.01-0.03 mol / L.

[0009] Furthermore, the preparation method of the wide temperature range ester-based electrolyte is: mix an organic solvent with deionized water, then add zinc salt and organic salt additives, and then mix them evenly by stirring and ultrasonic treatment.

[0010] The present invention also provides application of the above-mentioned wide temperature range ester-based electrolyte in aqueous zinc ion batteries.

[0011] The present invention also provides an aqueous zinc ion battery, comprising a wide-temperature range ester-based electrolyte, a positive electrode, a negative electrode and a separator.

[0012] Furthermore, the diaphragm is a sulfonic acid modified diaphragm, and its preparation method is: polyethersulfone, polyvinyl pyrrolidone, polyethylene glycol, polyetheretherketone, polyvinylidene fluoride and dimethylacetamide are mixed in a mass ratio of 2.5-3.5:0.5:0.2:0.2:0.1:16, and stirred and heated at 60-70°C for 1-5h to dissolve to obtain a spinning solution, which is then loaded into a syringe and electrospun at room temperature. The working voltage during spinning is 19kV, the working flow rate is 1.5mL / h, and the distance between the needle and the collector is 18cm to obtain a sulfonic acid modified diaphragm.

[0013] The beneficial effect of adopting a further technical solution is that the sulfonic acid modified diaphragm can effectively inhibit the shuttle effect of iodine in the aqueous zinc-iodine battery, which is beneficial to increase the service life of the aqueous zinc-ion battery and improve the stability of its cycle performance.

[0014] The present invention has the following beneficial effects:

[0015] 1. The wide temperature range ester-based electrolyte of the present invention adopts conventional medicines, has a simple preparation method, and the raw materials used are cheap and easily available. It can be obtained by a simple dissolution method, and then applied to aqueous zinc ion batteries to show good reversibility, high safety and excellent electrochemical performance.

[0016] 2. The wide-temperature-range ester-based electrolyte of the present invention has excellent electrochemical properties: the symmetrical zinc battery prepared using it exhibits excellent cycle stability and a wide operating temperature range, with stable cycle times of 2300, 2700 and 700 hours at 25°C, -25°C and 50°C, respectively; the Zn / / Cu half-cell prepared using it also exhibits ultra-high coulombic efficiency, with stable cycle times of 2300, 1000 and 1000 hours at 25°C, -25°C and 50°C, respectively; the Zn / / I2 full battery prepared using it shows higher stable cyclability and capacity retention rate than the full battery using pure zinc perchlorate electrolyte.

[0017] 3. Ammonium o-sulfobenzoate inhibits the growth of zinc dendrites and the corrosion phenomenon associated with active water on the zinc negative electrode by forming a solid electrolyte interface layer on the zinc surface, promotes uniform zinc ion flux, helps to extend the service life of aqueous zinc ion batteries, and improves the electrochemical performance of the battery. BRIEF DESCRIPTION OF THE DRAWINGS

[0018] Figure 1 This is a comparison chart of the long cycle of the symmetrical zinc battery assembled with the electrolyte of Example 1 and Comparative Example 1 at room temperature 25°C;

[0019] Figure 2 This is a comparison chart of long cycles of symmetrical zinc batteries assembled with the electrolytes of Example 1 and Comparative Example 1 at a high temperature of 50°C;

[0020] Figure 3 This is a comparison chart of the long cycle of the symmetrical zinc battery assembled with the electrolyte of Example 1 and Comparative Example 1 at a low temperature of -25°C;

[0021] Figure 4 A comparison chart of the coulombic efficiency of Zn / Cu half-cells assembled with the electrolytes of Example 1 and Comparative Example 1;

[0022] Figure 5 This is a SEM scan of the negative zinc sheet of the symmetrical zinc battery assembled with the electrolyte of Comparative Example 1 after 50 cycles at 25°C;

[0023] Figure 6 This is a SEM scan of the negative zinc sheet of the symmetrical zinc battery assembled with the electrolyte of Comparative Example 1 after 50 cycles at 50°C;

[0024] Figure 7 This is a SEM scan of the negative zinc sheet of the symmetrical zinc battery assembled with the electrolyte of Comparative Example 1 after 50 cycles at -25°C;

[0025] Figure 8 This is a SEM scan of the negative zinc sheet of the symmetrical zinc battery assembled with the electrolyte of Example 1 after 50 cycles at 25°C;

[0026] Fig. 9 This is a SEM scan of the negative zinc sheet of the symmetrical zinc battery assembled with the electrolyte of Example 1 after 50 cycles at 50°C;

[0027] Fig.10 This is a SEM scan of the negative zinc sheet of the symmetrical zinc battery assembled with the electrolyte of Example 1 after 50 cycles at -25°C;

[0028] Fig.11 XRD images of the negative electrode zinc sheet of the symmetrical zinc battery assembled with the electrolyte of Example 1 and Comparative Example 1 after 50 cycles at 25°C;

[0029] Fig.12 A comparison chart of the strength of the Zn(002) crystal plane and the Zn(100) crystal plane of the negative electrode zinc sheet after the symmetrical zinc battery assembled with the electrolyte of Example 1 and Comparative Example 1 was cycled for 50 cycles at 25°C;

[0030] Fig.13 The LSV curves obtained for the electrolytes of Example 1 and Comparative Example 1;

[0031] Fig.14 This is an electron photo of the sulfonic acid group-modified diaphragm;

[0032] Fig.15 This is the SEM scan of the sulfonic acid group modified diaphragm;

[0033] Fig.16 This is an in-situ optical microscope image of the sulfonic acid group-modified membrane;

[0034] Fig.17 Long cycle diagram of Zn / / I2 full battery assembled with electrolytes of Example 1 and Comparative Example 1 at 2C current density. DETAILED DESCRIPTION

[0035] The principles and features of the present invention are described below, and the examples are only used to explain the present invention and are not used to limit the scope of the present invention. If no specific conditions are specified in the embodiments, they are carried out according to normal conditions or conditions recommended by the manufacturer. If the manufacturer of the reagents or instruments is not specified, they are all conventional products that can be purchased commercially.

[0036] Example 1

[0037] A wide temperature range ester-based electrolyte comprising the following components: zinc salt, deionized water, an organic solvent and an organic salt additive;

[0038] Among them, the organic solvent is diethylene glycol ethyl ether acetate, and its volume fraction in the electrolyte is 40%; the organic salt additive is ammonium o-sulfobenzoate, and its concentration in the electrolyte is 0.02 mol / L; the zinc salt is zinc perchlorate hexahydrate, and its concentration in the electrolyte is 1.5 mol / L.

[0039] Example 2

[0040] A wide temperature range ester-based electrolyte comprising the following components: zinc salt, deionized water, an organic solvent and an organic salt additive;

[0041] Among them, the organic solvent is diethylene glycol ethyl ether acetate, and its volume fraction in the electrolyte is 20%; the organic salt additive is ammonium o-sulfobenzoate, and its concentration in the electrolyte is 0.01 mol / L; the zinc salt is zinc perchlorate hexahydrate, and its concentration in the electrolyte is 0.5 mol / L.

[0042] Example 3

[0043] A wide temperature range ester-based electrolyte comprising the following components: zinc salt, deionized water, an organic solvent and an organic salt additive;

[0044] Among them, the organic solvent is diethylene glycol ethyl ether acetate, and its volume fraction in the electrolyte is 60%; the organic salt additive is ammonium o-sulfobenzoate, and its concentration in the electrolyte is 0.03 mol / L; the zinc salt is zinc perchlorate hexahydrate, and its concentration in the electrolyte is 3 mol / L.

[0045] Example 4

[0046] An aqueous zinc ion battery comprises the wide temperature range ester-based electrolyte of embodiment 1, a positive electrode, a negative electrode and a separator.

[0047] Comparative Example 1

[0048] An electrolyte is a 1.5 mol / L zinc perchlorate hexahydrate solution.

[0049] Test Example 1

[0050] The electrolytes of Example 1 and Comparative Example 1 were used to assemble a Zn / Zn symmetric cell and a Zn / Cu half-cell, respectively. -2 and an area capacity of 0.5 mAh cm -2 The cycle number of the symmetrical battery and the coulombic efficiency of the half cell were tested under the following conditions.

[0051] (1) The long cycle comparison of the symmetrical zinc battery assembled using the electrolyte of Example 1 and Comparative Example 1 at room temperature 25°C is shown in the figure below. Figure 1 As shown in the figure, it can be seen that after adding organic solvents and organic salt additives, the cycle life of the battery is significantly extended compared to when no additives are added.

[0052] (2) The long cycle comparison of the symmetrical zinc battery assembled using the electrolyte of Example 1 and Comparative Example 1 at high temperature 50°C is shown in the figure below. Figure 2 As shown in the figure, it can be seen that after adding organic solvents and organic salt additives, the cycle life of the battery is significantly extended compared to when no additives are added.

[0053] (3) The long cycle comparison of the symmetrical zinc battery assembled using the electrolyte of Example 1 and Comparative Example 1 at low temperature -25°C is shown in the figure below. Figure 3 As shown in the figure, it can be seen that after adding organic solvents and organic salt additives, the cycle life of the battery is significantly extended compared to when no additives are added.

[0054] (4) The coulombic efficiency comparison of Zn / Cu half-cells assembled using the electrolytes of Example 1 and Comparative Example 1 is shown in the figure below. Figure 4As shown in the experimental results, it can be observed that the battery with organic solvent and organic salt additives has a lower Zn content in the charge and discharge cycle. 2+ The ion insertion and deinsertion process became more reversible, and after 2,300 cycles, its Coulombic efficiency reached almost 100%.

[0055] (5) The scanning electron microscope images of the negative electrode zinc sheet of the symmetrical zinc battery assembled using the electrolyte of Comparative Example 1 after 50 cycles at 25°C, 50°C and -25°C are as follows: Figure 5-7 As shown in the figure, it can be clearly seen that the deposition of zinc ions on the zinc surface is uneven and there are a large number of zinc dendrites. In addition, a large number of byproducts with polygonal structures are obviously accumulated on the surface of the zinc foil.

[0056] The scanning electron microscope images of the negative electrode zinc sheet of the symmetrical zinc battery assembled using the electrolyte of Example 1 after 50 cycles at 25°C, 50°C and -25°C are as follows: Figure 8-10 As shown in the figure, it can be clearly seen that the zinc ions are evenly covered on the zinc foil, making its surface smooth and uniform, which shows that the added organic salt additive effectively inhibits the growth of dendrites and the formation of by-products.

[0057] (6) The XRD images of the negative electrode zinc sheet of the symmetrical zinc battery assembled using the electrolytes of Example 1 and Comparative Example 1 after 50 cycles at 25°C are as follows: Fig.11 As shown in the figure, it can be clearly seen that the battery assembled with the electrolyte of Comparative Example 1 can clearly find the peak of the by-product Zn5(OH)8Cl2·xH2O. After adding ammonium o-sulfobenzoate and diethylene glycol ethyl ether acetate, the peak intensity of the by-product is significantly reduced, which shows that ammonium o-sulfobenzoate and diethylene glycol ethyl ether acetate can effectively inhibit the generation of by-products.

[0058] Furthermore, the intensity comparison diagram of Zn(002) crystal plane and Zn(100) crystal plane is shown in Fig.12 As shown. It can be clearly seen that for the electrolyte of Comparative Example 1, the ratio of Zn (002) crystal plane to Zn (100) crystal plane is 2.04. After adding ammonium o-sulfobenzoate and diethylene glycol ethyl ether acetate, the ratio can be increased to 2.60, proving that ammonium o-sulfobenzoate and diethylene glycol ethyl ether acetate can effectively promote the selective deposition of zinc ions on the Zn (002) crystal plane, thereby forming a uniform zinc coating.

[0059] (7) The LSV curves obtained using the electrolytes of Example 1 and Comparative Example 1 are as follows: Fig.13It can be clearly seen that the hydrogen evolution potential of the electrolyte to which ammonium o-sulfobenzoate and diethylene glycol ethyl ether acetate are added is significantly higher than that of the electrolyte in Comparative Example 1, proving that ammonium o-sulfobenzoate and diethylene glycol ethyl ether acetate can effectively inhibit the occurrence of hydrogen evolution side reaction in aqueous electrolyte.

[0060] Test Example 2

[0061] Polyethersulfone, polyvinyl pyrrolidone, polyethylene glycol, polyetheretherketone, polyvinylidene fluoride and dimethylacetamide were mixed in a mass ratio of 3:0.5:0.2:0.2:0.1:16, and dissolved by stirring and heating at 65°C for 4 hours to obtain a spinning solution, which was then loaded into a syringe and electrospun at room temperature. The working voltage during spinning was 19 kV, the working flow rate was 1.5 mL / h, and the distance between the needle and the collector was 18 cm to obtain a sulfonic acid modified diaphragm.

[0062] (1) Electron photo of sulfonic acid modified diaphragm Fig.14 As shown in the figure, it can be clearly seen that the separator is flexible, has a uniform white color as a whole, and can be bent and folded, ensuring its flexible adaptability and good mechanical properties in the battery.

[0063] (2) SEM scanning images of sulfonic acid modified diaphragm Fig.15 As shown, it can be clearly seen that the diaphragm presents a fibrous filament structure.

[0064] (3) In situ optical microscopy images of sulfonic acid modified diaphragms Fig.16 As shown, it can be clearly seen that the thickness of the diaphragm is about 62 μm.

[0065] (4) The long cycle image of the Zn / / I2 full battery assembled with electrolyte, sulfonic acid modified separator and iodine positive electrode at 2C current density is shown in the figure. Fig.17 As shown. It can be clearly seen that compared with the electrolyte of Comparative Example 1, the full battery assembled using the electrolyte containing ammonium o-sulfobenzoate and diethylene glycol ethyl ether acetate exhibits a higher reversible capacity, and after 1200 charge and discharge cycles, its cycle stability shows more significant superiority.

[0066] In summary, the wide temperature range ester-based electrolyte prepared by the present invention can effectively protect the zinc negative electrode and effectively inhibit the formation of dendrites and the occurrence of side reactions such as corrosion when used in aqueous zinc ion batteries. This innovation not only significantly increases the service life of aqueous zinc ion batteries, but also greatly improves the stability of their cycle performance. This is of great significance for promoting the industrial-scale production of aqueous zinc ion batteries.

[0067] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modification, equivalent substitution or improvement made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.

Claims

1. A wide temperature range ester-based electrolyte, characterized in that: The method comprises the following components: zinc salt, deionized water, organic solvent and organic salt additive; The organic solvent is diethylene glycol ethyl ether acetate; The organic salt additive is ammonium o-sulfobenzoate.

2. The wide temperature range ester-based electrolyte according to claim 1, characterized in that: The zinc salt is zinc perchlorate hexahydrate, and the concentration of the zinc salt in the electrolyte is 0.5-3 mol / L.

3. The wide temperature range ester-based electrolyte according to claim 1, characterized in that: The volume fraction of the organic solvent in the electrolyte is 20%-60%.

4. The wide temperature range ester-based electrolyte according to claim 1, characterized in that: The concentration of the organic salt additive in the electrolyte is 0.01-0.03 mol / L.

5. The wide temperature range ester-based electrolyte according to claim 1, characterized in that: The preparation method comprises the following steps: mixing the organic solvent with deionized water, adding the zinc salt and the organic salt additive, and mixing the mixture uniformly by stirring and ultrasonic treatment.

6. Use of the wide temperature range ester-based electrolyte according to any one of claims 1 to 6 in an aqueous zinc ion battery.

7. An aqueous zinc ion battery, characterized in that: It comprises the wide temperature range ester-based electrolyte as claimed in claim 1, a positive electrode, a negative electrode and a separator.

8. The aqueous zinc ion battery according to claim 7, characterized in that: The diaphragm is a sulfonic acid modified diaphragm, and its preparation method is: polyethersulfone, polyvinyl pyrrolidone, polyethylene glycol, polyetheretherketone, polyvinylidene fluoride and dimethylacetamide are mixed in a mass ratio of 2.5-3.5:0.5:0.2:0.2:0.1:16, and stirred and heated at 60-70°C for 1-5h to dissolve to obtain a spinning solution, which is then loaded into a syringe and electrostatically spun at room temperature. The working voltage during spinning is 19kV, the working flow rate is 1.5mL / h, and the distance between the needle and the collector is 18cm, so as to obtain the sulfonic acid modified diaphragm.

Citation Information

Patent Citations

  • Cathode for lithium ion secondary battery, lithium ion secondary battery, electric power tool, electrical vehicle, and electric power storage system

    CN102148357A

  • Wide-temperature-range aqueous zinc metal battery electrolyte and battery

    CN115588785A

  • Preparation method and application of low-temperature-resistant zinc ion battery electrolyte

    CN116315155A

  • Double-salt-double-solvent electrolyte for high-reversible aqueous zinc ion battery and preparation method of double-salt-double-solvent electrolyte

    CN117728047A

  • Non-aqueous electrolyte and secondary battery using the same

    JP2002158035A

Cited By

  • Electrolyte for improving floating charge performance of zinc-nickel battery as well as preparation method and application of electrolyte

    CN121642211A

  • Eutectic electrolyte based on ionic liquid and application of eutectic electrolyte in aqueous zinc-iodine battery

    CN122118133A